THE EFFECTIVENESS OF CROSSWORD PUZZLES WITH VARIED CLUES TYPES ON VOCABULARY MASTERY AMONG SECONDARY SCHOOL STUDENTS IN JEMBER - Anisa Intama; Kristi Nuraini; Muhlisin Rasuki (Premise: Journal of English Education and Applied Linguistics, 2026)
This study examines the effectiveness of crossword puzzles that integrate various type of clues in improving vocabulary mastery among secondary school students in an EFL learning environment. Vocabulary learning in the classroom can be challenging, as students have limited opportunities to interact with English. On the other hand, empirical research focusing on teaching strategies with structured instructional support is also limited. Therefore, this study aims to examine whether using of crossword puzzles that integrate varied clue types can support vocabulary learning. This study employed a pre-experimental one group pretest-posttest design, supported by qualitative data collected through questionnaires. Because the distribution of vocabulary test scores was not normal, non-parametric analysis was performed. Qualitative findings indicate that clues integrated into crossword puzzles support students, including definitions, synonyms, antonyms, fill-in-the-blanks, and pictures with letter clues in each grid, which help students recall the target vocabulary they have learned, in turn increase their confidence during the activity. The results of the study indicate that crossword puzzles with varied clue types improved students’ vocabulary development and engagement in a rural EFL classroom. In practice, the findings suggest that teachers may adapt crossword puzzles with varied clue types as a low-cost accessible strategy to support vocabulary learning in contexts where exposure to English and instructional resources are limited.